The current state of control loop performance monitoring – A survey of application in industry. (February 2016) - Bauer, Margret; Horch, Alexander; Xie, Lei; Jelali, Mohieddine; Thornhill, Nina
Abstract: Control loop performance monitoring (CPM) in industrial production processes is an established area of research for which many methods to detect malfunctioning loops have been developed. However, it is unclear which methods are successful in an industrial environment. Often, there are additional aspects such as organizational issues, data availability and access that can compromise the use of CPM. In this paper, we are reporting on the results of a survey amongst CPM users. The survey takes stock of existing methods and their use in industry as well as which faults are most frequent and can be detected. Organizational as well as implementation issues are investigated and discussed. This paper aims to identify open research topics and the direction of development of CPM in industrial production processes.